Balancing conservatism and innovation: The pragmatic Analects - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2013)
At the age of 14, I picked up a copy of the Analects for the first time.1 A quickbrowse revealed content that reminded me so much of my mother’s lectures aboutproper behavior that I promptly put it aside as a tract of old fashioned thinking andconservative manners. Through my early adulthood, my feelings about Chineseculture were close enough to the May Fourth intellectuals’ sensibilities that I didnot question interpretations of the Analects, and more generally Confucianism,as teaching a kind of conservatism incompatible with modern life. However,subsequent study has convinced me that such interpretations are one-sided andoften motivated by ideologies that misunderstood or misappropriated Confucius’thinking. This is not to deny that there are elements of conservatism in Confucius’teachings in the Analects, and even more in the traditions that grew around thetext, but the meaning of that “conservatism” (perhaps “conservatisms”) is neitherstraightforward nor simple, nor is it always opposed to innovation in all forms. Thischapter will explore the tension between the conservative and the innovativetendencies in the text.